Characterization of Strength and Function in Ambulatory Adults With GNE Myopathy. Issue 1 (September 2017) - Argov, Zohar; Bronstein, Faye; Esposito, Alicia; Feinsod-Meiri, Yael; Florence, Julaine M.; Fowler, Eileen; Greenberg, Marcia B.; Malkus, Elizabeth C.; Rebibo, Odelia; Siener, Catherine S.; Caraco, Yoseph; Kolodny, Edwin H.; et al.
Abstract: Objective: To characterize the pattern and extent of muscle weakness and impact on physical functioning in adults with GNEM. Methods: Strength and function were assessed in GNEM subjects (n = 47) using hand-held dynamometry, manual muscle testing, upper and lower extremity functional capacity tests, and the GNEM-Functional Activity Scale (GNEM-FAS). Results: Profound upper and lower muscle weakness was measured using hand-held dynamometry in a characteristic pattern, previously described. Functional tests and clinician-reported outcomes demonstrated the consequence of muscle weakness on physical functioning. Conclusions: The characteristic pattern of upper and lower muscle weakness associated with GNEM and the resulting functional limitations can be reliably measured using these clinical outcome assessments of muscle strength and function.